Introductory study of critical success factors for activity based costing implementation in manufacturing industry [compact disc] - 177501 Md. Mizreen Mohamed Sadek (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal) - Universiti Teknologi Malaysia, 2006